Effects of electroconvulsive therapy on cerebral A1 adenosine receptor availability: a PET study in patients suffering from treatment-resistant major depressive disorder - Kroll, Tina; Grözinger, Michael; Matusch, Andreas; Elmenhorst, David; Novakovic, Ana; Schneider, Frank; Bauer, Andreas (Frontiers in Psychiatry, 2023)
Introduction Sleep deprivation and electroconvulsive therapy (ECT) effectively ameliorate symptoms in major depressive disorder (MDD). In rodents, both are associated with an enhancement of cerebral adenosine levels, which in turn likely influence adenosinergic receptor expression. The aim of the current study was to investigate cerebral A1 adenosine receptor (A1AR) availability in patients with MDD as a potential mediating factor of antidepressant effects of ECT using [18F]CPFPX and positron emission tomography (PET). Methods Regional A1AR availability was determined before and after a series of ECT applications (mean number ± SD 10.4 ± 1.2) in 14 subjects (4 males, mean age 49.5 ± 11.8 years). Clinical outcome, measured by neuropsychological testing, and ECT parameters were correlated with changes in A1AR availability. Results ECT had a strong antidepressive effect (p < 0.01) while on average cerebral A1AR availability remained unaltered between pre-and post-ECT conditions (F = 0.65, p = 0.42, mean difference ± SD 3.93% ± 22.7%). There was no correlation between changes in clinical outcome parameters and regional A1AR availability, although individual patients showed striking bidirectional alterations of up to 30–40% in A1AR availability after ECT. Solely, for the mean seizure quality index of the applied ECTs a significant association with changes in A1AR availability was found (rs = −0.6, p = 0.02). Discussion In the present study, therapeutically effective ECT treatment did not result in coherent changes of A1AR availability after a series of ECT treatments. These findings do not exclude a potential role for cerebral A1ARs in ECT, but shift attention to rather short-termed and adaptive mechanisms during ECT-related convulsive effects.